Osteosarcomatous Transformation in the Setting of Mazabraud's Syndrome: A Case Report and Review of the Literature. (28th May 2019) - Multani, Iqbal; Popovic, Snezana; Parasu, Naveen; Ghert, Michelle
Abstract : Introduction . Mazabraud's Syndrome is a rare condition that is defined by the presence of fibrous dysplasia lesions in the bone and intramuscular myxomas in the soft tissue. Malignant transformation, in the setting of Mazabraud's Syndrome, of the fibrous dysplasia lesions into a sarcomatous neoplasm occurs in less than 1% of cases—with only six previously reported cases. Case Presentation . Here, we present a 62-year-old Caucasian female who developed an osteosarcoma in a fibrous dysplasia lesion of the proximal femur in the background of Mazabraud's Syndrome. The patient was treated with wide excision and endoprosthetic reconstruction. She declined adjuvant chemotherapy. She is alive without evidence of disease one-year postoperatively. Conclusion . Patients with Mazabraud's Syndrome remain at low risk for malignant transformation. However, close monitoring of asymptomatic patients with this condition for radiographic changes in their lesions and/or clinical symptoms is recommended.